Sleep apnoea in Australian men: disease burden, co-morbidities, and correlates from the Australian longitudinal study on male health. (October 2016) - Senaratna, Chamara; English, Dallas; Currier, Dianne; Perret, Jennifer; Lowe, Adrian; Lodge, Caroline; Russell, Melissa; Sahabandu, Sashane; Matheson, Melanie; Hamilton, Garun; Dharmage, Shyamali
Abstract Background Obstructive sleep apnoea is a common disorder with under-rated clinical impact, which is increasingly being recognised as having a major bearing on global disease burden. Men are especially vulnerable and become a priority group for preventative interventions. However, there is limited information on prevalence of the condition in Australia, its co-morbidities, and potential risk factors. Methods We used data from 13, 423 adult men included in the baseline wave of Ten to Men, an Australian national study of the health of males, assembled using stratified cluster sampling with oversampling from rural and regional areas. Those aged 18–55 years self-completed a paper-based questionnaire that included a question regarding health professional-diagnosed sleep apnoea, physical and mental health status, and health-related behaviours. Sampling weights were used to account for the sampling design when reporting the prevalence estimates. Odds ratios were used to describe the association between health professional-diagnosed sleep apnoea and potential correlates while adjusting for age, country of birth, and body-mass index (BMI). Results Prevalence of self-reported health professional-diagnosed sleep apnoea increased from 2.2 % in age 18–25 years to 7.8 % in the age 45–55 years. Compared with those without sleep apnoea, those with sleep apnoea had significantly poorer physical, mental, and self-rated health as well as lower subjective wellbeing and poorer concentration/remembering (p  < 0.001 for all). Sleep apnoea was significantly associated with older age (p  < 0.001), unemployment (p  < 0.001), asthma (p  = 0.011), chronic obstructive pulmonary disease/chronic bronchitis (p  = 0.002), diabetes (p  < 0.001), hypercholesterolemia (p  < 0.001), hypertension (p  < 0.001), heart attack (p  < 0.001), heart failure (p  < 0.001), angina (p  < 0.001), depression (p  < 0.001), post-traumatic stress disorder (p  < 0.001), other anxiety disorders (p  < 0.001), schizophrenia (p  = 0.002), overweight/obesity (p  < 0.001), insufficient physical activity (p  = 0.006), smoking (p  = 0.005), and high alcohol consumption (p  < 0.001). Conclusion Health professional-diagnosed sleep apnoea is relatively common, particularly in older males. Associations between sleep apnoea and cardiovascular, metabolic, respiratory, and psychiatric disorders have important clinical and public health implications. As men are especially vulnerable to sleep apnoea as well as some of its chronic co-morbidities, they are potentially a priority group for health interventions. Modifiable lifestyle related factors such as smoking, alcohol consumption, level of physical activity and BMI are possible key foci for interventions.